Nest-site selection and nesting success in the Azure-winged Magpie in Central Spain - Alonso, J A; Muñoz-Pulido, R; Bautista, L M; Alonso, J C (Bird Study, 1991)
Nest-site selection and nesting success in Azure-winged Magpies Cyanopica cyana were studied in 1986 in central Spain. Preferred nest sites were a nonrandom subset of the available habitat. Nests built on evergreen trees had significantly earlier clutch initiation dates than those built on deciduous trees. Birds selected larger trees of each species for nesting, but nests built on very high trees had significantly lower nesting success. Birds tended to locate their nests in a central position relative to the canopy height and as far from the main trunk as possible, without being of the periphery. This may minimize nest accessibility and maximize concealment. Nesting success was higher in the preferred regions of the tree canopy. Predation and inclement weather were probably the factors selecting for the observed patterns in nest-site distribution.
doi: 10.1080/00063659109477066
Keywords: Canopy; Cyanopica cyana; Evergreen and deciduous species (voyant); Nest site selection; Nesting success